1995
DOI: 10.1016/0304-3959(94)00203-q
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in pain ratings and pupil reactions to painful pressure stimuli

Abstract: In order to investigate gender differences in pain perception, the present study employed both a psychophysical and a psychophysiological measure. In experiment 1, 20 subjects rated the painfulness of 4 different levels of tonic pressure applied to their fingers using a verbally anchored categorization procedure. In general agreement with studies of pain threshold and tolerance, female subjects reported greater pain at high levels of stimulation, with no gender difference being evident at low pressure levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
135
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(144 citation statements)
references
References 20 publications
6
135
1
1
Order By: Relevance
“…Another potential source of bias in the study arises from the slightly higher (though not statistically significant) frequency of men in the Hemi-Sync group compared with the other groups. Though the widely held belief that women have a higher pain threshold than men has been reported [24], most studies either found no sex difference in pain perception [25] or reported a higher pain threshold for men than for women [26]. We were unable to detect any significant effect of gender on the doses of fentanyl required when our data were analysed both for all study patients and for the Hemi-Sync patients alone.…”
Section: Discussionmentioning
confidence: 65%
“…Another potential source of bias in the study arises from the slightly higher (though not statistically significant) frequency of men in the Hemi-Sync group compared with the other groups. Though the widely held belief that women have a higher pain threshold than men has been reported [24], most studies either found no sex difference in pain perception [25] or reported a higher pain threshold for men than for women [26]. We were unable to detect any significant effect of gender on the doses of fentanyl required when our data were analysed both for all study patients and for the Hemi-Sync patients alone.…”
Section: Discussionmentioning
confidence: 65%
“…It was also shown that pain-rating behavior could be influenced and that, when a gender-specific expectation of pain tolerance was given before the test, there were no longer significant gender differences in pain tolerance (56). Combined with the results of Ellermeier & Westphal (52), these findings show that women not only detect pain at an earlier stage, but are also more willing to report a stimulus as being painful. For our present study, this finding may imply that women simply more often report (relatively small) symptoms that are unrelated to exposure, while men report the more severe symptoms caused by exposure.…”
Section: Explaining Gender Differencesmentioning
confidence: 75%
“…Many laboratory studies have been performed to examine gender differences in pain perception. Women were found to have a lower pain threshold, independent of the exact stimulus, for example, thermal stimuli (hot and cold) (48)(49)(50), electrocutaneous stimulation (51), and pressure (52). This difference in pain perception has been attributed to the influence of sex hormones (53) and gender role expectations (54).…”
Section: Explaining Gender Differencesmentioning
confidence: 99%
“…20,57 In addition to measures that rely on subjective response, sex differences have been observed in physiological measures of pain response. Women experienced greater pupil dilation in response to a mechanical stimulus 16 and the spinal cord mediated nociceptive flexion reflex was elicited at lower intensity of electrical stimuli for women. 21 Collectively, this literature provides strong evidence that women have a greater response to pain, at least when stimuli are applied in a standard manner.…”
mentioning
confidence: 92%